Transcriptomic and Histological Analysis of Exacerbated Immune Response in Multidrug-Resistant Pseudomonas aeruginosa in a Murine Model of Endophthalmitis - Naik, Poonam; Pandey, Suchita; Naik, Milind N.; Mishra, Dilip Kumar; Boyenpally, Sreedhar Rao; Joseph, Joveeta (Frontiers in Immunology, 2022)
Multidrug-resistant (MDR) endophthalmitis is a serious threat to the whole spectrum of therapeutic procedures associated with the risk of managing and preventing vision loss. We have earlier shown the interplay of immune mediators in patients with MDR Pseudomonas aeruginosa (PA) endophthalmitis leading to worse outcome. Expanding on these findings, a murine model of endophthalmitis was developed to explore the effects of drug resistance on the pathogenesis by analyzing the temporal changes in retinal morphology along with its transcriptomic signatures. Clinical isolates of susceptible (S-PA) and multidrug-resistant PA (MDR-PA) were injected intravitreally in C57BL/6 mice followed by enucleation at 6h and 24h time points post-infection. Disease progression and retinal changes were monitored by clinical and histological assessment and transcriptome analysis in a pair-wise manner. Histological assessment of MDR-PA eyeball revealed higher disease severity (p <0.05), CD45+ cells (p= 0.007), MPO+ cells (p= 0.01) GFAP+ (p= 0.02), along with higher retinal cell death in mice infected with MDR-PA (p= 0.008). Temporal Transcriptome analysis revealed differential expression of nearly 923 genes at 6h p.i. and 2220 genes at 24h p.i. (FC ≥ 2, adjusted p-value < 0.05). Pathway enrichment analysis identified differentially regulation of chemokine and cytokine mediated, MAPK and NF-кβ signaling pathways. In conclusion, rapid deterioration of retinal architecture and immune exacerbation was significantly associated with the MDR endophthalmitis, suggests the need for immunomodulatory agents, to strengthen host cell functions, and support antibiotics to save the retinal structure from inevitable deterioration and restoration of the vision.